Keterampilan Berkomunikasi Siswa Melalui Penerapan Pembelajaran Kooperatif Tipe TGT (Teams Games Tournament) Kelas XII MAN 1 Mataram - sholehah, Najah (BIO-EDU: Jurnal Pendidikan Biologi, 2024)
Communication skills are the abilities that students have in conveying information, opinions, or news to other parties or individuals in a straightforward manner. Communication skills are an important requirement in the learning process because they can help and facilitate students to express ideas and exchange information with teachers or fellow students. The purpose of this study was to determine the effect of the TGT (Teams Games Tournament) type of cooperative learning model on improving the communication skills of class XI MAN 1 Mataram students. This study used a quasi-experimental research method with a quantitative approach. The sample used was students of class XI IPA 3 and XI IPA 4 MAN 1 Mataram. The hypothesis test used to determine the level of students' communication skills is the t-test. The results showed that the significance value for the NA of students' communication skills was 0.01 <0.05, so it could be concluded that there was an influence of the application of the TGT type cooperative learning model on the communication skills of class XI MAN 1 Mataram students.